The Effect of a Culture-Based mHealth Application “Bersama Peduli” on Pain, Sleep, and Fatigue Among Cancer Patients - Joko Supriyanto; Nur Chayati (Jurnal Ners, 2026)
Cancer patients commonly experience complex clusters of psychological and physiological symptoms, particularly pain, sleep disturbances, and fatigue. These symptoms require comprehensive and continuous management. This study introduced an innovative, non-pharmacological approach using a culture-based mobile health (mHealth) application Bersama Peduli to support primary symptom management. The study aimed to evaluate the effect of the Bersama Peduli mHealth application on pain, sleep quality, and fatigue among cancer patients. A quasi-experimental design with a one-group pre-test–post-test approach was employed. The sample consisted of 36 patients aged 18–75 years, selected through purposive sampling. Pain intensity was assessed using the Visual Analog Scale (VAS), sleep disturbances using the Pittsburgh Sleep Quality Index (PSQI), and fatigue using the Functional Assessment of Chronic Illness Therapy–Fatigue (FACIT–F). Measurements were taken over a four-week intervention period. Data were analyzed using the Wilcoxon test. The findings demonstrated significant improvements in pain, sleep disturbances, and fatigue, with all outcomes showing p-values of 0.001 (p < 0.05). These results indicate that the culture-based mHealth application Bersama Peduli effectively reduces pain, improves sleep quality, and decreases fatigue among cancer patients. Integration of this intervention into comprehensive cancer care strategies is strongly recommended.